Assessing the efficacy and acceptability of an internet-delivered intervention for resilience among college students: A pilot randomised control trial protocol - Richards, Derek; Enrique, Angel; Mooney, Olwyn; Salamanca-Sanabria, Alicia; Lee, Chi Tak; Farrell, S. (My University, 2019)
Background: Exposure to new stressors places college students at increased risk for developing mental health problems. Preventive interventions aimed at enhancing resilience have the potential to improve mental health and well-being in college students and internet-delivery may improve access to these interventions. However, few studies have evaluated the efficacy of online interventions for resilience in college students. The present study seeks to assess the feasibility [initial efficacy and acceptability] of a newly developed internet-delivered intervention for resilience provided with human or automated support, in a sample of college students. Method: A pilot randomised controlled trial including three groups: 1) an intervention group with human support; 2) an intervention group with automated support; and 3) a waiting list control group. The intervention, Space for Resilience, is based on positive psychology and consists of seven modules, delivered over a period of eight weeks. Primary outcomes measures will include the Connor-Davidson Resilience Scale (CD-RISC) and the Pemberton Happiness Index (PHI). Secondary outcomes measures will include the Brief Resilience Scale (BRS), the Patient Health Questionnaire – 4 items (PHQ-4), the Rosenberg Self-Esteem Scale (RSES), and the Perceived Stress Scale – 4 items (PSS-4). Acceptability will be examined using the Satisfaction with Treatment (SAT) questionnaire. Analysis will be conducted on an intention-to-treat basis. Discussion: The study seeks to establish the initial efficacy and acceptability of an internet-delivered intervention for resilience with human support and automated support. Apart from determining the impact of the intervention on acceptability and effectiveness, this study will be a first to explore more clearly the relative benefits of different support modes.
PUBLISHED
Keywords: Internet-delivered treatment; Resilience; Well-being; Positive psychology; Automated support; Human support; College students; Digital Engagement; RANDOMISED-CONTROLLED TRIAL; internet-delivered interventions; positive psychology; resilience; Mental Health/Psychosocial disability